Effect of suturing technique on corneal xenograft survival - Sedlakova, Klara; Filipec, Martin (Cornea, 2007)
PURPOSE: Understanding xenograft rejection is crucial for the potential introduction of xenotransplantation into clinical practice. Small-animal models play an essential role in this context and substantially contribute to our knowledge about mechanisms of xenograft rejection. METHODS: Rat-to-mouse corneal xenografts were performed by using 2 suturing techniques. Sutures were left either as long or as short as possible to limit the extent of a nonspecific inflammatory response. Cyclosporine A (CsA), monoclonal antibody anti-T cells, and a specific inhibitor of inducible NO synthase (alone or in a combination with CsA) were tested as immunosuppressants. RESULTS: Grafts with long sutures were rejected in 7.3 +/- 1.2 days, whereas those with short sutures were rejected after 11.8 +/- 1.0 days (P < 0.001). Similarly, long sutures induced more pronounced corneal neovascularization (P < 0.001). Although groups of recipients with long sutures all tested immunosuppressants significantly (P < 0.01-0.001) prolonged corneal graft survival, none of them showed a comparable efficacy in groups of recipients with short sutures. CONCLUSIONS: This study showed that suturing technique significantly affects the outcome of corneal concordant xenograft transplantation, influences the effectiveness of immunosuppressive regimens, and therefore must be taken into account when evaluating their efficacy.
Keywords: Animals; potkani inbrední LEW; Thy-1 Antigens; synthasa oxidu dusnatého, typ II; rohovka; thiaziny; Antibodies, Monoclonal; Cornea; Corneal Transplantation; Immunosuppressive Agents; cyklosporin; Mice; Thiazines; transplantace heterologní; Mice, Inbred BALB C; Transplantation, Heterologous; Suture Techniques; myši; transplantace rohovky; modely nemocí na zvířatech; myši inbrední BALB C; Cyclosporine; antigeny Thy-1; Disease Models, Animal; Graft Survival; krysa rodu Rattus; Nitric Oxide Synthase Type II; monoklonální protilátky; šicí techniky; zvířata; Rats, Inbred Lew; přežívání štěpu; Rats; imunosupresiva